IL-1 receptor signaling in the basolateral amygdala modulates binge-like ethanol consumption in male C57BL/6J mice - Marshall, S. Alex (Brain Behav Immun, 2015)
Proinflammatory cytokines have been implicated in alcohol-induced neurodegeneration, but the role of the neuroimmune system in alcohol related behaviors has only recently come to the forefront. Herein, the effects of binge-like drinking on IL-1β mRNA and immunoreactivity within the amygdala were measured following the “drinking in the dark” (DID) paradigm, a model of binge-like ethanol drinking in C57BL/6J mice. Moreover, the role of IL-1 receptor signaling in the amygdala on ethanol consumption was assessed. Results indicated that a history of binge-like ethanol drinking promoted a significant increase of IL-1β mRNA expression within the amygdala, and immunohistochemistry analyses revealed that the basolateral amygdala (BLA), but not central amygdala (CeA), exhibited significantly increased IL-1β immunoreactivity. Fluoro-Jade® C labeling indicated that multiple cycles of the DID paradigm were not sufficient to elicit neuronal death. Bilateral infusions of IL-1 receptor antagonist (IL-1Ra) reduced ethanol consumption when infused into the BLA but not the CeA. These observations were specific to ethanol drinking as the IL-1Ra did not alter either sucrose drinking or open-field locomotor activity. The current findings highlight a specific role for IL-1 receptor signaling in modulating binge-like ethanol consumption and indicate that proinflammatory cytokines can be induced prior to dependence or any evidence of neuronal cell death. These findings provide a framework in which to understand how neuroimmune adaptations may alter ethanol consumption and therein contributing to alcohol abuse.